Practical Experience Applying Feature‐based Product Line Engineering in a DevOps Environment: Achieving the Best of Both Worlds. Issue 1 (26th September 2022) - Pedone, Chris; Hartley, David; Darbin, Rowland; Clements, Paul
Abstract: Systems and Software Product Line Engineering (PLE) is an engineering discipline to produce and maintain a family of similar products in an efficient manner. It has long been known that managing a product portfolio as a single entity, as opposed to a multitude of separate products, can bring substantial improvements in schedule, cost, and quality. DevOps is an engineering discipline, practiced within an infrastructure of test and deployment automation, that seeks to minimize the time that a change to a product is made, and the product is built, validated, deployed, and made available to the end users. Many organizations find themselves willing to employ both disciplines – that is, to employ DevOps for products in a product line. This paper shows how that can be done, relates a case where it was done, and reports on the substantial benefits that were realized.